Flow synthesis of a versatile fructosamine mimic and quenching studies of a fructose transport probe - Matthew B. Plutschack; D. Tyler McQuade; Giulio Valenti; Peter H. Seeberger (Beilstein Journal of Organic Chemistry, 2013)
We describe the synthesis of 1-amino-2,5-anhydro-D-mannose (“mannitolamine”), a key intermediate to the 7-nitro-1,2,3-benzadiazole conjugate (NBDM), using commercially available fluidic devices to increase the throughput. The approach is the first example of a flow-based Tiffeneau–Demjanov rearrangement. Performing this step in flow enables a ~64-fold throughput enhancement relative to batch. The flow process enables the synthesis to be accomplished three times faster than the comparable batch route. The high throughput enabled the production of larger quantities of the fluorescent fructose transport probe NBDM, enabling us to measure key photophysical properties that will facilitate future uptake studies.